A novel homozygous GFI1B variant in 2 sisters with thrombocytopenia and severe bleeding tendency. (4th July 2021) - Brøns, Nanna; Zaninetti, Carlo; Ostrowski, Sisse Rye; Petersen, Jesper; Greinacher, Andreas; Rossing, Maria; Leinøe, Eva
Abstract: Genetic variants in growth factor-independent 1B ( GFI1B ), encoding transcription factor GFI1B, are causative of platelet-type bleeding disorder-17. Presently, 53 cases of GFI1B associated inherited thrombocytopenia (IT) have been published, however only three were homozygous. The bleeding- and platelet phenotypes of these patients depend on location and inheritance pattern of the GFI1B variant. We report a novel homozygous GFI1B (Thr174Ile) variant located in the first Zinc finger domain of GFI1B in two sisters of Palestinian ancestry born to consanguineous parents. They experienced severe bleeding tendency at moderately reduced platelet counts. Flow cytometry and immunofluorescent microscopy confirmed the diagnostic features of GFI1B associated IT: a reduced content of alpha granules and aberrant expression of the stem cell marker CD34 on platelets. Transcription factor GFI1B is differentially expressed during hemato- and lymphopoiesis. In addition, to platelet function investigations, we present results of lymphoid subgroup analyses and deformability of red cells measured by ektacytometry.